2008
DOI: 10.1186/1471-2334-8-117
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic influenza in Australia: Using telephone surveys to measure perceptions of threat and willingness to comply

Abstract: Background: Baseline data is necessary for monitoring how a population perceives the threat of pandemic influenza, and perceives how it would behave in the event of pandemic influenza. Our aim was to develop a module of questions for use in telephone health surveys on perceptions of threat of pandemic influenza, and on preparedness to comply with specific public health behaviours in the event of pandemic influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
159
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(187 citation statements)
references
References 12 publications
18
159
4
2
Order By: Relevance
“…This finding was inconsistent with a study conducted by Barr et al (2008) and found that there were no differences between the perceptions of men and women. However it was matched with another study that was done in USA and found that women were more likely to be concerned about the spread of swine flu than men.…”
Section: Discussioncontrasting
confidence: 75%
“…This finding was inconsistent with a study conducted by Barr et al (2008) and found that there were no differences between the perceptions of men and women. However it was matched with another study that was done in USA and found that women were more likely to be concerned about the spread of swine flu than men.…”
Section: Discussioncontrasting
confidence: 75%
“…They also found that education had an effect on the difference between the genders [12]. Barr et al reported that in 200 families surveyed by the New South Wales Department of Health, the risk perception during an avian influenza pandemic was 45.5% especially for themselves and their families [21]. In our study, we did not find a significant difference between genders when we evaluated the risk perception of the study group.…”
Section: Discussioncontrasting
confidence: 48%
“…The perception of nonspecialist people apart from the scientific and technical view for the risks is not objective [20]. In various studies, different risk perception results have been found [9,12,21]. Rubin et al, in their study performed at the beginning of a pandemic, found that the risk perception of the public is very high (21%) [9].…”
Section: Discussionmentioning
confidence: 99%
“…This is often attributed to a sense of invulnerability in young people, resulting in higher levels of risk-taking behaviour. Older people were more likely to report that they would perform self-protective behaviours in the event of a future avian influenza outbreak or future influenza pandemic (Lau, 2007;Barr, 2008). A potential explanation may be that older people feel more susceptible to being affected by disease (Barr, 2008) and that this personal vulnerability may be projected to their horses, resulting in higher levels of biosecurity compliance.…”
Section: Discussionmentioning
confidence: 99%